ZEOLITE X SYNTHESIS FROM COAL FLY ASH AND ITS APPLICATION FOR NI, ZN, AND CU ADSORPTION - Camilia Nabila, Jihan
Coal combustion in electricity generation produces solid waste in the form of fly ash and basic ash which are categorized as B3 waste. Until now, coal fly ash has been widely used as raw material for cement. The content of aluminosilicate in fly ash has the potential to be used as raw material for making zeolites. This will result in the added value of fly ash. This study aims to synthesize zeolite X from coal fly ash. This research is divided into two stages of the process, namely pre-treatment and synthesis experiments. The pre-treatment stage consisted of calcination of coal fly ash at 850oC for 2 hours, treated with hydrochloric acid (HCl) at 90oC for 1 hour, and aqua DM at 90oC for 1 hour twice. The method used in this synthesis is fusion alkaline-hydrothermal. The fusion stage was carried out by the addition of NaOH, then calcined at 550oC for 2 hours. The aging process is carried out on an incubator shaker. Then, the hydrothermal process is carried out at a temperature of 110oC for 12 hours. Variations were made on the ratio of NaOH : coal fly ash, aging time, and Si and Al ratio. The zeolite X characterization was carried out using XRD, SEM, and BET tests. The results of this study show that the initial impurity content of coal fly ash is reduced by the presence of pretreatment, such as Fe2O3 from 19.04% to 12.24%, CaO from 17.37% to 2.95%, and MgO from 7.49% to 2.00%. This research succeeded in synthesizing zeolite X, with some impurities such as zeolite A, zeolite Na-P1, and zeolite P-A. The zeolite surface area is 11-39 m2/g and the crystallinity is between 22% and 62%. The increase of NaOH and fly ash ratio up to 1.2 rises the zeolite crystallnity. However, the increase until 1.6 result in lower crystallinity of zeolite. The growth of Si and Al ratio decrease the crystallinity of zeolite. The 16 hours-aging-time is able to stimulate higher zeolite crystallinity. Zeolite X has a 99.74% adsorption ability on Ni2+ metals with a concentration of 100 ppm.